Exploratory search on big data - Xiao-yong DU; Jun CHEN; Yue-guo CHEN (Tongxin xuebao)
Exploratory search is a new approach for discovering the value of big data,compared with data serving and data analysis.Data serving emphasizes to meet users' information need at the micro-level,and data analysis emphasizes to discover insights among data at the macro-level.However,exploratory search is a way to support user to freely swap between micro-level to macro-level and interactively explore the value of data as well.Firstly,approaches for discovering the value of big data were discussed.Secondly,the definition,model and characteristics of exploratory search were illustrated.Thirdly,the architecture of exploratory search systems was designed,and a review of the challenges and techniques of each component of the architecture were given.Finally,preliminary results of exploratory search in RDF knowledge bases were introduced.